Previous treatment influences fingolimod efficacy in relapsing–remitting multiple sclerosis: results from an observational study. (September 2014) - Baldi, Eleonora; Guareschi, Angelica; Vitetta, Francesca; Senesi, Caterina; Curti, Erica; Montepietra, Sara; Simone, Anna Maria; Immovilli, Paolo; Caniatti, Luisa; Tola, Maria Rosaria; Pesci, Ilaria; Montanari, Enrico; et al.
Abstract Objective: Fingolimod (FTY) is licensed as a disease-modifying treatment in highly active relapsing–remitting multiple sclerosis. The aim of the study was to evaluate the efficacy and safety of FTY in a real-life setting and to explore the possible role of clinical and MRI parameters, including previous treatment type, in predicting its efficacy. Methods: Clinical and MRI data was collected on 127 patients assigned to treatment with FTY in six multiple sclerosis centers in Emilia-Romagna, Italy, between August 2011 and June 2013. Results: During a mean follow-up period of 10 months (range 1–22), we observed a total of 47 relapses in 39 patients (30.7%); new T2 lesions or gadolinium-enhancing (Gd+) lesions were present at follow-up MRI in 32/71 patients (45%). Expanded disability status scale (EDSS) at the end of the follow-up period was not different when compared to the baseline EDSS. Serious adverse events occurred in three patients (2.4%). A higher proportion of patients previously treated with natalizumab showed clinical (41%) or MRI activity (54%). Previous treatment with natalizumab increased the risk of a relapse within 30 days (versus immunomodulatory drugs; OR: 4.3; p = 0.011) and at survival analysis (versus remaining patients; HR: 1.9; p = 0.046). Study limitations include a small population sample, a short observation period with variable timing of follow-up MRI and different baseline characteristics of patients previously treated with natalizumab compared to those treated with immunomodulatory drugs. Conclusions: This study confirms the efficacy of FTY in reducing relapse rate in patients previously treated with immunomodulatory drugs, while it seems to be less effective in patients discontinuing natalizumab. Due to the short duration of follow-up it is not possible to evaluate disability progression; however, no difference was observed between the groups.